ROLE OF FEEDBACK IN INTENSIVE LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the essential role of feedback in intensive language learning environments. Feedback, both corrective and formative, guides learners toward greater language accuracy and fluency. The article investigates how timely, specific, and constructive feedback enhances learner motivation, supports self-regulation, and builds confidence. Emphasis is placed on teacher-student interaction, peer feedback, and technology-based responses. The analysis highlights how feedback transforms passive learning into an active process and contributes to accelerated progress in intensive language programs.